Effect of fermented Banana peel on Broiler Carcass - TNI, Koni (Indonesian Journal of Animal and Veterinary Sciences, 2013)
This experiment was conducted to examine effect of inclusion of fermented banana peel by Rhyzopus oligosporus in diets on slaughter weight, carcass weight Â and carcass percentage, weight and percentage abdominal fat of broiler. The experiment was done based on Completely Randomized Design with four treatments and four replications and each replication consisted of six chickens. The treatment were R0 = without banana peel fermented, R1 = 5% banana peel fermented, R2 = 10% banana peel fermented, R3 = 15% banana peel fermented. Data of the experiment were analyzed, using ANOVA and then continued with Duncans Multiple Range Test. Result showed that level of fermented banana peel affected slaughter weight and carcass weight. However carcass persentage, weight and percentage of abdominal fat was not affected by treatment. Banana peel fermented by Rhizopus oligosporus could can be used maximally 10% in broiler ration. Key Words: Banana Peel, Rhyzopus oligosporus, Slaughter Weight, Carcass Weight, Abdominal Fat